2000
DOI: 10.1063/1.1288812
|View full text |Cite
|
Sign up to set email alerts
|

Discharge efficiency in plasma displays

Abstract: The dependence of the panel efficacy of an alternating current-surface-discharge plasma display on the input power is investigated. Test panels with a design resembling the one used in main stream commercial products are used. The input power is varied in two ways: namely by changing the dielectric layer capacitance (thickness) and by changing the sustain voltage. An interesting different behavior is found: for increasing capacitance the efficacy decreases markedly, whereas for increasing sustain voltage the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 3 publications
3
35
0
Order By: Relevance
“…The breakdown extinguishes when the local electrical field, determined by the sum of the electrical field of the accumulated charges and the applied field, becomes lower than the breakdown field. DBDs are widely used for ozone generation, for surface treatment, for pollution control, for excimer lamps 22 and for plasma display panels, 23 and have attracted extensive research. 24 It should be pointed out that DBDs in ferroelectrets are different from the commonly studied ones ͑these studies are usually dedicated to discharge phenomena in a single dielectric-barrier gap͒ because of the numerous voids in cellular ferroelectrets with their often rather wide size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The breakdown extinguishes when the local electrical field, determined by the sum of the electrical field of the accumulated charges and the applied field, becomes lower than the breakdown field. DBDs are widely used for ozone generation, for surface treatment, for pollution control, for excimer lamps 22 and for plasma display panels, 23 and have attracted extensive research. 24 It should be pointed out that DBDs in ferroelectrets are different from the commonly studied ones ͑these studies are usually dedicated to discharge phenomena in a single dielectric-barrier gap͒ because of the numerous voids in cellular ferroelectrets with their often rather wide size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that PDPs with high-Xe-content gas mixtures have the potential for improving luminous efficiency under a conventionally used driving scheme. 11,12 The luminous efficiency exhibits a step-wise increase by increasing the sustain voltages especially for higher-Xe contents. The luminous efficiency increases linearly to total pressure.…”
Section: Introductionmentioning
confidence: 99%
“…10 shows the most important energy levels and transitions for Xe. The generation of the Xe excitation states Xe*(1s 4 ) and Xe*(1s 5 ) include three kinds of processes: 21,25 (1) electron impact excitation directly from the ground state (shown by the gray arrows); (2) heavy body collisions with Xe**(2p 5-10 ), Xe*(1s 2 ), or Xe*(1s 3 ) by the Ne or Xe atoms (shown by the magenta arrows); (3) radiative processes by Xe**(2p [1][2][3][4] or Xe**(2p 5-10 ) (shown by the green arrows). The processes related to NIR and VUV radiation, which are concerned with in this section, are marked in the diagram.…”
Section: B 2d Simulationsmentioning
confidence: 99%
“…INTRODUCTION Recently, the improvement of luminous efficacy in the PDPs towards the goal of "5 lm/W" is achieved by using various advanced technologies. [1][2][3][4][5][6][7][8] However, comparing with the fluorescent lamp that is able to reach the luminous efficacy of 60 lm/W, the gap in plasma display panel (PDP) is still huge. This becomes especially clear when observing the difference in the VUV production efficiency: compared with the other VUV emitting plasma devices, like the fluorescent lamps, the small discharge space of PDP limits the VUV production efficiency of PDP to a level of only 0.1, compared with about 0.6 for a fluorescent lamp.…”
mentioning
confidence: 99%